Garfield (2012), volume 4 ebook - Davis, Jim (Garfield (2012), 2015)
The good times continue to roll in this next collection of Garfield comic book stories! In this round, we see how the gang beats the heat, learn if Jon can finally stop being late, and if Nermal can set a world record! Also, Pet Force stops by!